Ergonomic analysis of book web services’ interfaces - Kłodnicka, Patrycja; Matraszek, Dawid (Journal of Computer Sciences Institute, 2025)
The success of a website depends heavily on the quality of an interface, which is assessed by a few factors: functionality, aesthetics, ergonomics. The objectives of this work's research are two web services dedicated to books, Lubimyczytać and Bookworm. In this study two experiments were conducted: eye tracking and a cognitive journey. In both cases, participants received a few problems to solve. Participants also filled out surveys that asked for their feedback. The research revealed issues with usability of the both interfaces. Lubimyczytać was found to be the winner of this comparison. In order to draw correct conclusions, it was necessary to take into consideration different aspects of examined applications: readability, web page’s logical layout. Mentioned points made tasks faster and easier to complete.